Uncertain Dynamical Systems - Martynyuk, A. A.; Martynyuk-Chernienko, Yu (Chapman and Hall/CRC, 2011)
This self-contained book provides systematic instructive analysis of uncertain systems of the following types: ordinary differential equations, impulsive equations, equations on time scales, singularly perturbed differential equations, and set differential equations. Each chapter contains new conditions of stability of unperturbed motion of the abo.